Compost amendment enhances leaf gas exchange, growth, and yield in water-challenged ‘Crimson Giant’ red radish (Raphanus sativus L.) - Alsadon, Abdullah; Dewir, Yaser Hassan; Ibrahim, Abdullah; Alenazi, Mekhled; Osman, Mohamed; Al-Selwey, Wadei A.; Ali, Mahmoud A.A.; Shady, Mohamed; Alsughayyir, Ali; Hakiman, Mansor (American Society for Horticultural Science, 2024)
Red radish is a nutritious root vegetable crop that has a short production cycle. Water deficit limits plant productivity, affecting its quantity and quality. Compost amendment offers a potential solution to mitigate water deficit effects. This study assessed the impact of compost manure rates (0, 50, 75, and 100) and irrigation treatments (40, 60, 80, and 100 of evapotranspiration) on ‘Crimson Giant’ red radish production. Significant differences in growth and quality were observed among these treatments. Compost rates of 75 and 100 improved leaf gas exchange, plant growth (leaf count, fresh weight, dry weight, and area; stem length), root development, total yield (root fresh weight, dry weight, diameter, and length), and root quality (vitamin C and total soluble solid and titratable acidity). The 100 compost and 100 irrigation combination achieved the highest yields. Under water deficit, applying 75 or 100 compost with 80 irrigation conserved 20 of water while maintaining radish output. Overall, compost amendment effectively enhanced red radish growth and production under water deficit.